MiR-3960 from Mesenchymal Stem Cell-Derived Extracellular Vesicles Inactivates SDC1/Wnt/β-Catenin Axis to Relieve Chondrocyte Injury in Osteoarthritis by Targeting PHLDA2. (25th August 2022) - Ye, Peng; Mi, Zhanhu; Wei, Daihao; Gao, Pengcheng; Ma, Mei; Yang, Haibo
Abstract : Osteoarthritis (OA) is a serious disease of the articular cartilage characterized by excessive inflammation. Lately, mesenchymal stem cell- (MSC-) derived extracellular vesicles (EVs) have been proposed as a novel strategy for the treatment of OA. We aimed to investigate the effects of EV-encapsulated miR-3960 derived from MSCs on chondrocyte injury in OA. The cartilage tissues from OA patients were collected to experimentally determine expression patterns of miR-3960, PHLDA2, SDC1, and β -catenin. Next, luciferase assay was implemented to testify the binding affinity among miR-3960 and PHLDA2. EVs were isolated from MSCs and cocultured with IL-1 β -induced OA chondrocytes. Afterwards, cellular biological behaviors and levels of extracellular matrix- (ECM-) related protein anabolic markers (collagen II and aggrecan), catabolic markers (MMP13 and ADAMTS5), and inflammatory factors (IL-6 and TNF- α ) in chondrocytes were assayed upon miR-3960 and/or PHLDA2 gain- or loss-of-function. Finally, the effects of miR-3960 contained in MSC-derived EVs in OA mouse models were also explored. MSCs-EVs could reduce IL-1 β -induced inflammatory response and extracellular matrix (ECM) degradation in chondrocytes. miR-3960 expression was downregulated in cartilage tissues of OA patients but enriched in MSC-derived EVs. miR-3960 could target and inhibit PHLDA2, which was positively correlated with SDC1 and Wnt/ β -catenin pathway activation. miR-3960 shuttled by MSC-derived EVs protected against apoptosis and ECM degradation in chondrocytes. In vivo experiment also confirmed that miR-3960 alleviated chondrocyte injury in OA. Collectively, MSC-derived EV-loaded miR-3960 downregulated PHLDA2 to inhibit chondrocyte injury via SDC1/Wnt/ β -catenin.